Multimarket contacts and bank profitability: Do diversification and bank ownership matter? - Tu Dq Le (Cogent Economics & Finance, 2020)
This study investigates the impact of multimarket contacts on bank profitability in the Vietnamese banking system from 2006 to 2015 using the system GMM. The findings indicate in general no evidence of the mutual forbearance hypothesis in this sector. However, we do find evidence of tacit collusion for the case of foreign-owned banks and newly combined banks with greater multimarket contacts. Finally, this study reveals that on average the most profitable banks are less geographically diversified, more technically efficient, and have lower credit risk. Regarding the role of bank ownership, more profitable banks are state-owned commercial banks, listed banks, and non-merged banks.
Keywords: G21; G28; G30; 330; bank ownership; diversification; GMM; Multimarket contact; profitability; Vietnam